2020
DOI: 10.15576/asp.fc/2020.19.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Concentrations and Loads of Total Phosphorus in Domestic and Treated Wastewater Over a 15-Year Observation Period in Terms of Limiting Negative Anthropopressure on the Quality of Surface Water – Case Study

Abstract: Aim of the studyThe main aim of the research was to verify the thesis that formal and legal restrictions on the use of phosphorus compounds, particularly polyphosphates, in detergents extensively introduced in recent years reduced the concentration and load of this nutrient in raw sewage inflowing to the selected treatment plant. Additionally, it was tested whether the phosphorus decreasing in raw sewage reduced the concentrations and loads of total phosphorus in treated sewage, and thus reduced negative sewag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In order to determine the amount of nonbiodegradable phosphorus intended for chemical precipitation, the formula (9) was used: It is proposed to use the PIX-113 coagulant for phosphorus precipitation (with the content of 11.8% Fe and the density gK = 1500 kg/m 3 ). The D K dose was calculated from the formula (10): In the first stage, the total V R volume of the nitrification and denitrification chambers was determined (formula 11): (11) where: C g -activated sludge concentration in the reactor -assumed 3.7 g dm/m 3 In order to calculate the volume of the V R bioreactor, the optimal concentration of the dry mass of the sediment C g was assumed based on the results of the calculations by Nowobilska-Majewska and Bugajski (2020).…”
Section: Resultsmentioning
confidence: 99%
“…In order to determine the amount of nonbiodegradable phosphorus intended for chemical precipitation, the formula (9) was used: It is proposed to use the PIX-113 coagulant for phosphorus precipitation (with the content of 11.8% Fe and the density gK = 1500 kg/m 3 ). The D K dose was calculated from the formula (10): In the first stage, the total V R volume of the nitrification and denitrification chambers was determined (formula 11): (11) where: C g -activated sludge concentration in the reactor -assumed 3.7 g dm/m 3 In order to calculate the volume of the V R bioreactor, the optimal concentration of the dry mass of the sediment C g was assumed based on the results of the calculations by Nowobilska-Majewska and Bugajski (2020).…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study are consis-tent with the results reported by Ton et at. (2008) and Kaczor (2020), where the TN concentration decreased by 10.1% to 27.46%.…”
Section: Efficiency Of the Anaerobic Digestermentioning
confidence: 95%
“…The results of this study are consis-tent with the results reported by Ton et at. (2008) and Kaczor (2020), where the TN concentration decreased by 10.1% to 27.46%.…”
Section: Efficiency Of the Anaerobic Digestermentioning
confidence: 95%